Pain, instability, and familial discord: a qualitative study into women who use drugs in Malaysia. Issue 1 (December 2015) - Rahman, Fifa; Lall, Priya; Iqbal, Sarah; Vicknasingam, B.
Abstract Background Out of 20, 887 persons who use drugs that came into contact with the National Anti-Drugs Agency (NADA) officials in the year 2013, 3.2 % were women. Because women who use drugs (WWUD) are often a hidden population, this may be an underestimate. International literature shows that women who use drugs face increased risk of HIV, intimate partner violence, and mental health issues. Similar literature in Malaysia is lacking, and thus, the objective of our study was exploratory in nature. Methods Thirty-eight women who use drugs were interviewed using a semi-structured topic guide in Kelantan, Penang, Johor, Kuala Lumpur, and Selangor. Locations were chosen purposively. Nineteen women were interviewed individually and the remaining 19 were in focus group discussions (FGDs). All interviews were transcribed verbatim, translated to English, and analyzed with NVivo. Results Median age of respondents was 35.5 years old, 89.5 % ethnic Malays, majority having married below the age of 20, and were of low socioeconomic backgrounds. Youngest age of initiation into drug use was 9 years old. Most reported is inhalation of amphetamine-type substances. Seven reported ever injecting. Three themes emerged: (a) repeating patterns of fluid family structures and instability; (b) "pain" and "difficulty" as features of home life; and (c) seeking marriage as a source of stabilization and practices of power within those marriages. Respondents often came from very fluid family environments and married to find stability, only to be drawn into a similar cycle. None of the women who had been separated from their children either institutionally, by family members, or by third parties, had accessed legal recourse for the loss of their parental rights. Conclusion Unstable familial relationships or environments contributed to earlier initiation of drug use which raised questions about support services for WWUD and children who use drugs. Respondents were drawn into unstable and/or abusive relationships, perpetuating social inequalities that marked their own familial environments during childhood. These findings support the need for additional services to support the unique needs of WWUD, including domestic violence services, financial and life skills, parental rights assistance, and empowerment programs.